CHOICE OF THERAPY OF POSTOPERATIVE NEUROLOGIC COMPLICATIONS AND PREVENTIVE MAINTENANCE OF DISTRESSES OF THE HIGHEST MENTAL FUNCTIONS BY CAROTID ENDARTERECTOMY - V. V. Shmelev; M. I. Neimark (Бюллетень сибирской медицины)
At patients with carotid endarterectomy the relative assessment of total intravenous anaesthesia with use propofol, penetrating blockage of a cervical plexus and inhalation sevofluran is made. Markers of cerebral damage, a state of the highest mental functions were investigated. It is shown that for each kind of anaesthesia are characteristic specific level neuronal damages that affects on a state of the highest mental functions, number and character of postoperative complications. In therapy of neurologic complications and preventive maintenance cognitive distresses clinical efficacy ceracson is shown.